Improving Public Speaking Skills at University Level through TED Talks Short Sessions - Aprilia, Rizma Ajeng (Universitas Negeri Surabaya, 2022)
For English learners, being able to speak English in public circumstances is a crucial thing in the process of delivering and retaining ideas both from speakers and listeners. Nevertheless, this course is often shunned from other language skills like listening, reading, and writing. It also creates feelings of anxiety toward learners. Even scholars argued that students studying English as a second or foreign language are having higher rates of experiencing problems. Thus, the researcher was eager to implement digital short supplementary material to university students to improve their performances in public speaking classes, namely TED Talks short session videos. This research aim was to investigate the effect of TED Talks on college students' public speakingperformances. The study took one month and a half to be finished and involved 40 participants as the sample from English Education freshmen of Universitas Negeri Surabaya. The students were divided into two groups, which were an experimental group and a control group. Under experimental pretest-posttest research design, the students were assessed on their speaking performances based on the components set in a speaking rubric. The data were analyzed using an independent sample t-test using SPSS 26. The results of the study showed that there was a difference in the outcome scores between the control group and experimental group which was significant. This was evidenced in the Independent Sample t-Test with a significance value of 0.00. Then, it was confirmed on the mean data in the experimental group which is 89.10 and the control group which is 83.60. The finding of this research revealed that TED talks short sessions can be constructive and beneficial to improve college students' public speaking performances